Chemical, mechanical, and thermal properties of UV-curable cellulose acetate butyrate-based oligomers and their electrospun fibrous mats - YILDIZ, ZEHRA (SPRINGER, 2020)
In this research, toluene diisocyanate-2-hydroxyethyl methacrylate (TDI-HEMA) adduct was used to modify the hydroxyl groups on cellulose acetate butyrate (CAB) structure. The obtained oligomer was characterized by Fourier transform infrared and proton nuclear magnetic resonance (H-1 NMR) spectroscopies, and gel permeation chromatography, respectively. Then, the UV-cured free films of the modified CAB oligomers were investigated in terms of thermal degradation, physicochemical, wettability, and mechanical properties. The chemical modification process was performed in various percentages; then, the contribution of the unreacted hydroxyl groups of CAB on the wettability, thermal degradation, and air/water vapor permeability properties were all investigated. The mechanical properties, thermal stability, and surface wettability character of pure CAB were improved with TDI-HEMA adduct modification. Electrospinning was used to obtain a fibrous layer in order to search the air/water vapor permeability properties. Modification of CAB caused decline in air/water vapor barrier character and thus enhanced the permeability properties.
Keywords: Cellulose acetate butyrate; UV curing; Electrospinning; Air; water vapor permeability; DIISOCYANATE; ACRYLATES